Информационно-аналитическая система Национального космического агентства Украины - Kolesnyk, V. I.; Smagliuk, V. V.; Volokh, K. F.; Kutsar, A. D. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper discusses the fundamental principles of developing the information and analytical system of the National Space Agency of Ukraine (IAS NSAU). Information obtained from space systems must be promptly applied to address a wide range of tasks. IAS NSAU, as an integrator of information resources, is designed for collecting, analyzing, and processing data received from both space-based and ground-based sources, as well as for the timely delivery of processed thematic information to relevant users.